A Scoping Insight on Potential Prophylactics, Vaccines and Therapeutic Weaponry for the Ongoing Novel Coronavirus (COVID-19) Pandemic- A Comprehensive Review - Dash, Priyanka; Mohapatra, Subhashree; Ghosh, Sayantan; Nayak, Bismita (Frontiers in Pharmacology, 2021)
The emergence of highly virulent CoVs (SARS-CoV-2), the etiologic agent of novel ongoing “COVID-19” pandemics has been marked as an alarming case of pneumonia posing a large global healthcare crisis of unprecedented magnitude. Currently, the COVID-19 outbreak has fueled an international demand in the biomedical field for the mitigation of the fast-spreading illness, all through the urgent deployment of safe, effective, and rational therapeutic strategies along with epidemiological control. Confronted with such contagious respiratory distress, the global population has taken significant steps towards a more robust strategy of containment and quarantine to halt the total number of positive cases but such a strategy can only delay the spread. A Substantial number of potential vaccine candidates are undergoing multiple clinical trials to combat COVID-19 disease, includes live-attenuated, inactivated, viral-vectored based, sub-unit vaccines, DNA, mRNA, peptide, adjuvant, plant, and nanoparticle-based vaccines. However, there are no licensed anti-COVID-19 drugs/therapies or vaccines that have proven to work as more effective therapeutic candidates in open-label clinical trial studies. To counteract the infection (SARS-CoV-2), many people are under prolonged treatment of many chemical drugs that inhibit the PLpro activity (Ribavirin), viral proteases (Lopinavir/Ritonavir), RdRp activity (Favipiravir, Remdesivir), viral membrane fusion (Umifenovir, Chloroquine phosphate (CQ), Hydroxychloroquine phosphate (HCQ), IL-6 overexpression (Tocilizumab, Siltuximab, Sarilumab). Mesenchymal Stem Cell therapy and Convalescent Plasma Therapy have emerged as a promising therapeutic strategy against SARS-CoV-2 virion. On the other hand, repurposing previously designed antiviral agents with tolerable safety profile and efficacy could be the only promising approach and fast response to the novel virion. In addition, research institutions and corporations have commenced the redesign of the available therapeutic strategy to manage the global crisis. Herein, we present succinct information on selected anti-COVID-19 therapeutic medications repurposed to combat SARS-CoV-2 infection. Finally, this review will provide exhaustive detail on recent prophylactic strategies and ongoing clinical trials to curb this deadly pandemic, outlining the major therapeutic areas for researchers to step in.